Trophic State of the Bakuok Lake, Aur Sati Village, Tambang District, Kampar Regency, Riau Province Based on Trophic State Index (TSI) - Sihombing, Susi; Simarmata, Asmika Harnalin; Siagian, Madju (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTSeveral activities in Bakuok Lake contributed the input of organic and anorganic matter that affects the water quality, especially nutrient concentration in waters. A research aims to understand the trophic state of Bakuok Lake based on TSI has been conducted in June-July 2019. There were three stations namely station 1 (plantation area), station 2 (residential area) and station 3 (fish cage area).In each station, there were 2 sampling points, in the surface (0.15 m) and 2 Secchi depth (1.74 m). Sampling were conducted 3 times, once/week. Water quality parameters measured were total phosphate, chlorophyll-a, transparancy, dissolved oxygen, CO2,pH and temperature. The value of water quality is as follows: the total phospatewas 0.10-0.22 mg/L, chlorophyll-a12.00-14.43 µg/L, transparency:58-87 cm, dissolved oxygen:6.57-7.54 mg/L, CO2:9.37-13.86 mg/L, pH: 5, temperature:29-31oC and TSI (Trophic State Index) value: 62.54-68.00. Based on TSI value, the Bakuok Lake can be categorized asmoderate to eutrophic.Keywords:Kampar River,Eutrophic, Oxbow Lake, Water Quality